THE EFFECTIVENESS OF HIDDEN OBJECT GAMES IN INCREASING VOCABULARY MASTERY OF EIGHTH GRADE STUDENTS AT SMPN 3 NGANJUK - Agustin Merdekawati; Sujono SUJONO (Journal of English Language Education, 2025)
Vocabulary mastery is a crucial component of English language learning that directly impacts students' communication skills. This study investigates the effectiveness of using Hidden Object Games (HOGs) as an innovative learning tool to improve the vocabulary mastery of eighth-grade students. Using a quantitative approach with a quasi-experimental design, this research involved 52 students divided into an experimental group (n=26) and a control group (n=26). The experimental group learned vocabulary through a Hidden Object Game application, while the control group used conventional methods. A vocabulary test was administered as a pre-test and post-test. Results showed the experimental group's average score increased significantly from 65.4 to 82.7, whereas the control group's average only rose from 64.2 to 68.9. Statistical analysis using an independent samples t-test yielded a t-count of 12.1, which exceeded the critical t-table value (1.708), indicating a statistically significant difference. The study concludes that Hidden Object Games are an effective method for enhancing vocabulary mastery among junior high school students. This is an open access article under the CC BY-SA License.